2022
DOI: 10.3389/fcimb.2022.818391
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effects of Neutrophil Elastase Inhibitor (Sivelestat) on Gut Microbiome and Metabolite Profiles of Septic Rats

Abstract: BackgroundNeutrophil elastase (NE) is associated with sepsis occurrence and progression. We hypothesized that the NE inhibitor Sivelestat might modulate abnormal gut microbiota and metabolites during sepsis.MethodsSixty Sprague-Dawley (SD) rats were randomly divided into sham control (SC), sepsis (CLP), and sepsis+Sivelestat (Sive) groups. The rats’ survival status was monitored for 24 hours postoperatively, and feces were collected for microbiome and non-targeted metabolomics analyses.ResultsSivelestat admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Because NE exhibited minimum bactericidal activity against periodontal pathogen, it has the potential to induce compositional changes that causes periodontitis severity. In addition, it was reported that administration of NE inhibitor in septic rats improved gut microbiota composition 34 . The composition of the oral microbiota closely related to the severity of periodontitis 35 , thus, further studies are required to determine the effects of NE and NE inhibitors on the oral microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Because NE exhibited minimum bactericidal activity against periodontal pathogen, it has the potential to induce compositional changes that causes periodontitis severity. In addition, it was reported that administration of NE inhibitor in septic rats improved gut microbiota composition 34 . The composition of the oral microbiota closely related to the severity of periodontitis 35 , thus, further studies are required to determine the effects of NE and NE inhibitors on the oral microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Reports in animal models of sepsis indicate that microbiota metabolites modulate outcomes (231)(232)(233) and implicate the gut microbiome in injury in multiple organs (234,235). Further, targeting the microbiome for therapeutic gain-by probiotics, prebiotics, synbiotics, microbial spores, fecal microbial transplantation, or selective decontamination of the digestive system-has been helpful in disorders such as dementia and cognitive disorders, inflammatory bowel disease, and lupus (236)(237)(238)(239)(240) and may have therapeutic benefit in sepsis (232,233,241). However, the contribution of the microbiome to sepsis pathobiology is underexplored (242), and the therapeutic potential of microbiota manipulation is untapped.…”
Section: Bts4: How Does the Microbiome Affect Sepsis Pathobiology? Ho...mentioning
confidence: 99%
“…The main examples of synthetic inhibitors are Sivelestat and β-lactam inhibitors, which are highly specific inhibitors with high potency and excellent permeability, that have demonstrated effects in reducing markers of lung lesions [83].…”
Section: Synthetic Hne Inhibitorsmentioning
confidence: 99%